2020
DOI: 10.1002/ece3.6996
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary history of endangered and relict tree species Dipteronia sinensis in response to geological and climatic events in the Qinling Mountains and adjacent areas

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 85 publications
0
10
0
Order By: Relevance
“…S11). Phylogeographic studies have revealed that the uplift of the Qinling Mountains played an important role in the genetic differentiation of many plant species in China (Guo et al, 2014;Xia et al, 2018;Shahzad et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…S11). Phylogeographic studies have revealed that the uplift of the Qinling Mountains played an important role in the genetic differentiation of many plant species in China (Guo et al, 2014;Xia et al, 2018;Shahzad et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The QM provides a natural boundary between northern and southern China, and served as a geographical and ecological barrier for species with low dispersal ability ( Yan et al, 2010 ; Hu et al, 2021 ). Its isolation also promoted the divergence of some relict species ( Shahzad et al, 2020 ). Mount Taibai, belonging to the QM, is the highest peak (3,500 m a.s.l.)…”
Section: Discussionmentioning
confidence: 99%
“…Due to the high geographic and environmental heterogeneity in central China, an IBD effect on genetic divergence has been found widely in some low to moderate altitude plant species, such as Dipteronia sinensis Oliv. (Shahzad et al, 2020), and Euptelea pleiosperma J. D. Hooker & Thomson (Meng et al, 2020). Our results indicate that the Qinling Mountains in East Asia comprised an important east–west isolation barrier that led to the intraspecific differentiation of the perennial alpine cold‐tolerant herb N .…”
Section: Discussionmentioning
confidence: 99%